KEGIATAN ASESMEN PADA SEKOLAH MENENGAH PERTAMA X JAKARTA - Debora Basaria; P.Tommy. Y.S.Suyasa; Zamralita Zamralita; Hanna Christina Uranus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The pandemic period brings various impacts in various sectors, one of which is in the field of education. Learning and teaching activities that usually take place face-to-face, now have to take place online. This causes the interaction between teachers and students, even students and their school friends to be limited. When students are still learning offline, students can ask questions and directly discuss with the teacher and their friends about materials that are not understood. However, when online learning is carried out, students become more reluctant to ask questions, are not motivated to attend classes, and find it difficult to focus, this has an impact on students' not optimal performance in academics and makes it difficult for them to recognize their potential. So this activity is intended to help the school and also students.This activity was attended by 139 students and students consisting of several levels, namely grades VII, VIII, and IX. Data collection using NEO-PI, Academic/ Non-Academic Self Concept, and School Inventory measuring instruments. In general, the results show that students at SMP Don Bosco II Jakarta have quite high anxiety and it is known that currently students have the highest interest in foreign language lessons. In addition, it is known that from 139 students 78% already have goals to be achieved and 22% of them still do not have goals to be achieved.